Most secret and confidential intelligence in the Age of Nelson - Maffeo, Steven E. (Naval Institute Press, 2000)
Reading at times like a cloak-and-dagger mystery, this book describes the ingenious methods used to collect and disseminate secret intelligence in the Age of Sail.